Alelopatia Causada por Espécies de Cerrado - Silveira, Jader Luís da (2021)
The objective of this work is to identify species from the cerrado biome that have allelopathic potential through field and laboratory study from soil collected in the vicinity of these species. In addition, it is intended to characterize the allelopathic potential of these native species through the germination of seeds of target species (lettuce and sorghum) in the presence of the soil near the plants and extracts obtained from these soils. And to identify the compounds that cause the inhibition of germination and / or seedling growth of the target species.